Social Capital and Community Resilience to Tidal Flooding: A Sociological Study in the Coastal Area of Pontianak City - Baharuddin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of social capital on community resilience in facing tidal flooding in Pontianak City, West Kalimantan. A mixed methods approach was used, combining a quantitative survey of 300 respondents and qualitative interviews with community leaders, fishermen, and village officials. Social capital variables were measured through the dimensions of trust, social networks, and mutual aid norms, while community resilience variables included adaptive capacity, collective capacity, access to resources, and post-disaster recovery. Quantitative analysis results indicate that social capital has a highly significant impact on community resilience, with an R² value of 0.974 and significance of 0.000. Dimensions of inter-resident trust, participation in social groups, and mutual aid norms were found to be dominant factors in strengthening coastal community resilience. Qualitative analysis reinforces these findings by describing adaptive and collective community responses, such as building stilt houses, activating mutual aid, and strengthening coordination with external parties such as the government and NGOs. Both quantitative and qualitative results indicate that social capital functions as a key mechanism in strengthening the resilience of Pontianak communities against tidal flooding. This study underscores that disaster risk reduction strategies in the coastal areas of West Kalimantan require not only structural interventions but also the strengthening of social capital as the foundation of community resilience